1986
DOI: 10.1111/j.1365-2184.1986.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement Split Product C5a Mediates the Lipopolysaccharide‐Induced Mobilization of Cfu‐S and Haemopoietic Progenitor Cells, But Not the Mobilization Induced By Proteolytic Enzymes

Abstract: Abstract. Intravenous (i.v.) injection of mice with lipopolysaccharide (LPS), and the proteolytic enzymes trypsin and proteinase, mobilizes pluripotent haemopoietic stem cells (CFU-s) as well as granulocyte-macrophage progenitor cells (GM-CFU) and the early progenitors of the erythroid lineage (E-BFU) from the haemopoietic tissues into the peripheral blood. We investigated the involvement of the complement (C) system in this process. It appeared that the early mobilization induced by LPS and other activators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…We noticed that while C3 (C3a, desArg C3a) cleavage fragments increase the retention of HSPCs in BM, C5 (C5a, desArg C5a) cleavage fragments enhance the egress of HSPCs into PB. This was evidenced in mobilization studies performed in C3-and C5-deficient animals which revealed that C3-deficient mice are easy mobilizers and C5-deficient mice poor mobilizers (Molendijk et al 1986;Ratajczak et al 2004a;Reca et al 2003;Reca et al 2007). …”
Section: Pharmacological Mobilization Of Hspcsmentioning
confidence: 95%
See 1 more Smart Citation
“…We noticed that while C3 (C3a, desArg C3a) cleavage fragments increase the retention of HSPCs in BM, C5 (C5a, desArg C5a) cleavage fragments enhance the egress of HSPCs into PB. This was evidenced in mobilization studies performed in C3-and C5-deficient animals which revealed that C3-deficient mice are easy mobilizers and C5-deficient mice poor mobilizers (Molendijk et al 1986;Ratajczak et al 2004a;Reca et al 2003;Reca et al 2007). …”
Section: Pharmacological Mobilization Of Hspcsmentioning
confidence: 95%
“…Fms-like tyrosine kinase 3, KL, vascular endothelial growth factor [VEGF]), and small molecular CXCR4 receptor antagonists (e.g. AMD3100, T140) (Andrews et al 1994;Hattori et al 2001;King et al 2001;Laterveer et al 1995;Liles et al 2003;Mohle et al 1998;Molendijk et al 1986;Papayannopoulou et al 1997;Ratajczak et al 2004a;Reca et al 2003). To obtain more efficient and faster mobilization, some of these compounds could be combined together (e.g.…”
Section: Pharmacological Mobilization Of Hspcsmentioning
confidence: 99%
“…Mobilization through G-CSF is associated with a decrease in heparanase levels and a concomitant increase of MMP-9 and cathepsins [34]. The exact role of other proteins, such as complement [35] and the fibrinolysis/plasminogen [36] system, has not been elucidated yet.The same proteolytic G-CSF-induced mechanism is responsible for the degradation of VCAM-1, fibronectin, and OPN, leading to reduced cellular adhesion of HSC through their receptor VLA-4 to BM stroma [28, 37]. …”
Section: Mechanisms Of Hsc Mobilizationmentioning
confidence: 99%
“…Mobilization through G-CSF is associated with a decrease in heparanase levels and a concomitant increase of MMP-9 and cathepsins [34]. The exact role of other proteins, such as complement [35] and the fibrinolysis/plasminogen [36] system, has not been elucidated yet.…”
Section: Mechanisms Of Hsc Mobilizationmentioning
confidence: 99%
“…C5 deficient A/J and C5 -/- mice show poor granuloma formation needed for containment of the infection and instead show a pneumonitis. Macrophages secrete a C5 peptidase, which cleaves C5 into C5a and C5b [12]. The most potent anaphylatoxin of the complement system is C5a, the 14 kDa cleavage product of C5.…”
Section: Introductionmentioning
confidence: 99%